Underlying Dimensions of Ecocentric and Anthropocentric Environmental Beliefs - Amérigo, María; Aragonés, Juan Ignacio; Frutos, Belinda De; Sevillano, Verónica; Cortés, Beatriz (The Spanish Journal of Psychology, 2007)
This study focuses on the cognitive components of general environmental attitudes. Taking as a starting point the scale of Thompson and Barton (1994) to identify ecocentric and anthropocentric motives in environmental conservation, the beliefs that guide attitudes in the person-environment relationship are analyzed. Confirmatory factor analysis was used to contrast the tripartite structure of these beliefs—based on egoistic, socioaltruistic, and biospheric aspects—with a two dimensional structure that confronts ecocentric and anthropocentric orientations. The results obtained from two samples, a student sample (n = 212) and a sample from the general population of Madrid (n = 205), indicate the existence of a three dimensional structure of environmental beliefs: an anthropocentric dimension based on the instrumental value of the environment for human beings, a biospheric dimension that values the environment for its own sake, and, lastly, an egobiocentric dimension that values the human being within nature as a whole.
Keywords: Environmental beliefs; Anthropocentrism; Ecocentrism; Self in nature